تقييم أداء البيئات الإفتراضية عند استخدام نظام التخزين التكراري المتماثل DRBD)) كجهاز تخزين مشترك في العنقود - قبلان, قاسم; خليل, حيدر (Latakia University Journal -Engineering Sciences Series, 2018)
إن البيئة الإفتراضية هي البنية الأساسية و المكون الأهم من مكونات الحوسبة السحابية و نظرا لما تقدمه البيئة الإفتراضية من ميزات لا تقدمها البيئات غير الإفتراضية من مرونة و توفير للطاقة والتكلفة و الاستخدام الأمثل للموارد جعل معظم شركات الاعمال و الحكومات تتجه لتحميل خدماتها و تطبيقاتها على مخدمات افتراضية بدلا من المخدمات الفيزيائية و من هذا المنطلق اتجه الباحثون لمقارنة اداء البيئات الإفتراضية المختلفة بهدف الحصول على أفضل بيئة ممكنة ليتم استخدامها في الحوسبة السحابية وتحقيق الحوسبة عالية الأداء. تم تقييم تأثير البيئة الافتراضية على "الحوسبة عالية الأداء كخدمة وذلك من خلال تغيير نوع البيئة الإفتراضية المستخدمة كبنية تحتية في الحوسبة السحابية . تم استخدام البيئة الإفتراضية XEN-PV( XEN Paravirtualization ) كبنية تحتية للحوسبة عالية الأداء و من ثم البيئة الإفتراضية (XEN-Hardware virtual machine) XEN-HVM حيث أن ال XEN هو ال hypervisor الأساسي لشركة Citrix وهي شركة رائدة في تطوير البيئات الإفتراضية وتم تقيم الأداء عند استخدام نظام التخزين التكراري المتماثل DRBD (Distributed Replicated Block Device ) كجهاز تخزين مشترك للأقراص الإفتراضية في العنقود. إن نتائج هذا البحث تثبت أن تقنية البيئة الافتراضية و مخطط العنقدة المستخدم لهما دور مهم في تحسين أداء "الحوسبة عالية الأداء". The Virtualization is the main structure, and the most important component from the others cloud computing components. Due to the features which are produced only from the virtual environment, such as flexibility, cost, energy saving, and the optimal usage of the resources, most business companies and the governments look ahead for deploying their services and applications on virtual severs instead of the physical ones. That point made the researchers heading toward performance comparing through different virtual environments. For reaching the best possible environment which is suitable to be used in the cloud computing, and to get the high performance computing. We described the effect evolution of the virtual environment on the high performance computing as a service, through changing the type of the used virtual environment in the infrastructures. We used the virtual environment XEN-PV ( XEN-Paravirtualization) as an infrastructures for the high performance. Lastly, I used the XEN-HVM (XEN HardWare virtual machine ), XEN is the main hypervisor in Citrix company and the performance has been evaluated by using DRBD as a shared storage of virtual disk. The results of our researches proved that both the virtual environment, and the selected clustering charts have a visible, important role in the performance of the “The high performance computing”.